Relief Borobudur: Catatan Visual Perjalanan Spiritual - Laurent, Lieke; Riyanti, Fitri; Kassapa, Kassapa; Lestari, Sarah Ayu; Widiyanto, Widiyanto (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2024)
Borobudur Temple, Relief Borobudur is a Buddhist temple in Central Java, Indonesia, recognized as one of the most important world heritage sites. The temple is famous for its magnificent architecture and richly meaningful reliefs. Borobudur is not only a place of worship, but also a spiritual symbol of Buddhism and the path to enlightenment. The temple structure consists of ten levels, reflecting the three realms of Buddhism: Kamadhatu (the realm of lust), Rupadhatu (the realm of form), and ARupadhatu (the realm of formlessness). The reliefs on the temples reflect Buddhism and the life of the people in the past, including hunting stories and traditional arts. The Karmawibhanga, Jataka-Awadana, and Gandawyuha reliefs tell about moral teachings and the law of karma, which emphasizes the principle of cause and effect in human life. The temple acts as a means of information about the past, presenting a picture of social and cultural life. After being rediscovered by Sir Thomas Stamford Raffles in the 19th century, Borobudur has undergone repeated restoration to ensure its preservation. In 1991, UNESCO designated the place as a World Heritage Site. Apart from being an extraordinary work of art, Borobudur also teaches about morality, concentration, and wisdom, making it a spiritual place that blends art and philosophy.Borobudur, Kamadhatu, Rupadhatu, ARupadhatu.